The Good Housekeeping Organic Handbook - Jaine, Tom (Petits Propos Culinaires, 2024)
The Good Housekeeping Organic Handbook: HarperCollins, London 2001: ISBN 0-00-711689-6: 190 pp., colour photos, h/b, £18.99.